(untitled) (Asian Education Studies, 2017)
The test of association of words and ideas proposed by Kent and Rosanoff, may be designed as a creative technique to study the mental operations selected by a population. This test has been carried out with two groups of Greek pupils in order to study the gap of the interpretations proposed from the term "watch", an object that is not found only in school, but that reminds to the rhythm of school life and by extension, to the employment of time regulating daily life. The test of association of words and ideas is of interest if one examines, on the one hand, the total of connotations produced by the students and if one compares, on the other hand, the statements of the two groups in relation to their level of studies and to their ability to combine unexpected ideas. The study of connotation for the study of the mechanism of the association of words and ideas from the inducing object of the watch can be used to draw conclusions on the type of mental operations carried out by the two groups of participants in distinguished social and personal areas. Finally, the scope of the interpretation of the inducing object suggested always remains open. Thus, the territory of the associated ideas remains unconquered and reveals the psychology and the inventiveness of the participants.